2018
DOI: 10.3389/fneur.2017.00742
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and Serum Hormone Levels Are Associated with Gray Matter Volume Decline in Female Patients with Prolactinomas

Abstract: Background and objectiveCognitive impairments have been reported in patients with hyperprolactinemia; however, there is a lack of knowledge of brain structure alterations relevant to hyperprolactinemia in prolactinomas. Thus, we aimed to identify changes in brain structure in prolactinomas and to determine whether these changes are related to cognitive performance and clinical characteristics.MethodsParticipants were 32 female patients with prolactinomas and 26 healthy controls (HC) matched for age, sex, educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
4
35
2
Order By: Relevance
“…Goto et al attributed grey matter shrinkage in the hippocampus to sex hormone levels. Indeed, studies have shown that certain types of hormones, such as PRL and E 2 , have an impact on the hippocampus . In the present study, a majority of the enrolled women had normal sex hormone levels and smaller age differences compared to previous studies .…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Goto et al attributed grey matter shrinkage in the hippocampus to sex hormone levels. Indeed, studies have shown that certain types of hormones, such as PRL and E 2 , have an impact on the hippocampus . In the present study, a majority of the enrolled women had normal sex hormone levels and smaller age differences compared to previous studies .…”
Section: Discussionsupporting
confidence: 43%
“…Indeed, studies have shown that certain types of hormones, such as PRL and E 2 , have an impact on the hippocampus. 27,50 In the present study, a majority of the enrolled women had normal sex hormone levels and smaller age differences compared to previous studies. 9,10 Therefore, our negative findings in the hippocampus may be caused by less demographic diversity and smaller hormonal fluctuations compared to the previous studies.…”
Section: Grey Matter Volume Changes and Correlation Analysiscontrasting
confidence: 44%
See 2 more Smart Citations
“…We have previously investigated the influence of endogenous 56 hormones on brain gray matter and neurocognition in prolactinoma patients. 1 However, functional 57 connections in prolactinoma patients have scarcely been explored. Recently, the resting-state 58 functional magnetic imaging (rsfMRI) has become a useful tool to characterize the brain's 59 functional connectivity (FC) pattern that is considered a potential metric reflecting the temporal 60 dependence of neuronal activation patterns of spatially separated brain areas.…”
Section: Introduction 53mentioning
confidence: 99%